Heritability, genetic gain, and correlations in cowpea bean (Vigna unguiculata [L.] (Walp.) (2021)
Cowpea beans are the most important legume in the Caribbean region of Colombia. This grain is produced mainly by small farmers in rural agriculture but is becoming more important every year for commercial agriculture. The objective of this study was to estimate heritability, genetic gain and correlations between agronomic characteristics and the nutritional content of 30 cowpea bean cultivars. The number of days to flowering (NDF), number of pods per plant (NPP), number of pods per peduncle (NPPE), peduncle length (PEL), number of nodes on main stem (NNMS), grain length (GL), grain width (GW), weight of 100 seeds (W100S), iron content (FeC), zinc content (ZnC), protein content in percentage (PROT) and YIELD were evaluated. Likewise, the genetic parameters: phenotypic coefficient of variation (PCV), genotypic coefficient of variation (GCV), variability index (b), heritability [(h2 (%)], genetic gain (GG) and genetic progress (%), together with phenotypic correlations and genetic correlations, were determined. Genetic variability was evidenced in the population (P<0.05), except for PEL. The highest heritability was in W100S, ZnC and FeC (h2A> 96%). The greatest advance was achieved in ZnC, FeC, W100S and YIELD, with values higher than 30%, indicating the potential use of the evaluated genotypes for improving this species and positive and significant phenotypic and genotypic correlations between YIELD and PROT. Therefore, cultivars with higher yields and protein contents can be obtained.